PANDANGAN MAHASISWA BIOLOGI TERHADAP PENGGUNAAN METODE FIELD TRIP DALAM MATA KULIAH ENTOMOLOGI - Wita Ferwati (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2019)
Entomology is a subject that studies about insects, so that students better understand the lecture material properly so we need to use the field trip method. The purpose of this research is to know the views of students biology for the use of the field trip method in the Entomology course. The research method used is descriptive. The population in this study were students who took the Entomology subject in even Semester 2018/2019 academic year totaling 14 students. Field trip was carried out in Kampung Sawah of Sampuran, Labuhan Batu, Rantau Prapat, North Sumatra, a forest area with rivers and waterfalls. The data collection technique was interviewed, and the data questionnaire was processed descriptively. The research results of students state that; a) strongly agree that learning activities using the field trip can increase knowledge and more understandable material as much as 86%; b) strongly agree that learning activities can increase interest by 71%; c) strongly agree that learning activities are more attractive by 79%; d) strongly agree that learning activities are not boring by 100%; e) strongly agree that learning activities are more fun as much as 100%; f) strongly agree that learning activities can foster a sense of concern for the environment by 79%; g) strongly agree that learning activities increase motivation by 80%.